The Impact of Family Setting and Local Opportunities on Leaving Home and Migration Destinations of Rural Youths, The Netherlands 1860-1940 - Bastian Mönkediek; Jan Kok; Kees Mandemakers (Historical Life Course Studies)
In this article we aim to study how Dutch children’s individual destinies result from the complex interplay of family setting and local conditions in a rural environment. We focus on their final move from the parental home, and we will analyse not only timing and incidence of leaving, but also the destinations. To do this, we propose a multi-level competing risk analysis of migration destinations. We focus on two groups: the children of farmers and those of rural workers. Dutch farmers and workers differ in the type of family economy in which children were integrated, and contrasting them will allow us to explain the speed, the directions, and the individual and family backgrounds of the process of leaving agriculture. We make use of the Historical Sample of the Netherlands to analyse last migrations of 8,338 children of farmers and rural workers. As we cover the entire country, we can study the full impact of regional differences on type of agriculture and inheritance, in combination with the family composition. Our results indicate significant effects of specialised versus traditional, mixed farming on the migration behaviour of farmers’ and rural workers’ children, as well as the importance of the number of siblings of the same sex and birth order. The variations in the effects of the sibship among regions with different agricultural systems demonstrate the importance of gender-specific divisions of labour on leaving home.